Cost-effectiveness of statin treatment for primary prevention in conditions of real-world adherence – Estimates from the Finnish prescription register. Issue 1 (March 2015) - Aarnio, Emma; Korhonen, Maarit J.; Huupponen, Risto; Martikainen, Janne
Abstract: Objective: To estimate the cost-effectiveness of statin therapy for primary prevention of coronary heart disease (CHD) events under real-world adherence. Methods: A cost-effectiveness model was applied to estimate the expected 10-year costs and health outcomes (in terms of quality-adjusted life-years, QALYs) associated with and without statin treatment (at defined adherence levels) among hypothetical cohorts of Finnish men and women who were initially without established CHD. Treatment efficacy, cost, and quality of life estimates were obtained from published sources. Long-term treatment adherence was measured based on data from the national prescription register. Results: At an assumed willingness-to-pay threshold of €20, 000 per QALY gained, statin treatment with real-world adherence was cost-effective among the older patient groups when the patients' 10-year CHD risk was as high as 20% and did not seem cost-effective in the youngest age groups. Conversely, statin treatment with full adherence was cost-effective for almost all patient groups with a 10-year CHD risk of at least 15%. Conclusions: Even though generic statins are now low-cost drugs, treatment adherence seems to have a major impact on the cost-effectiveness of statin treatment in primary prevention. This finding stresses the importance of making a concerted effort for improving adherence among patients on statin therapy to obtain full benefit of the investment in statins. Therefore, novel cost-effective approaches to improve treatment adherence are warranted. Highlights: We estimated the cost-effectiveness of statin therapy under real-world adherence. Adherence seems to have a major impact on the cost-effectiveness of statin therapy. Statins do not seem cost-effective for low-risk patients even with full adherence. Ways to improve adherence among patients on statin therapy are needed.